2023
DOI: 10.1111/ahe.12919
|View full text |Cite
|
Sign up to set email alerts
|

Pelvis shape analysis with geometric morphometry in crossbreed cats

Abstract: Pelvis is the bone roof formed by articulation of right and left coxae (os ilium, os ischii, os pubis) at the level of ventromedian (König et al., 2007;Özcan & Demiraslan, 2021). Linea terminalis is the imaginary line that separates the abdominal cavity and the pelvic cavity and extends along the line passed through the anatomical points called as ala sacralis, tuberculum musculus psoas minoris, eminentia ilio pubica, respectively. Thus, the limits of the entrance of the pelvic cavity are formed (Bahadir & Yil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Similar results were found in dogs, mirroring those observed in horses. Additionally, it was reported that the entrance to the pelvic cavity in male cats is narrower than in females, and the crista iliaca is located more laterally in males (Manuta et al, 2023). Compared to this study, the narrowing of the pelvic cavity is similar to that in cats in male dogs.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Similar results were found in dogs, mirroring those observed in horses. Additionally, it was reported that the entrance to the pelvic cavity in male cats is narrower than in females, and the crista iliaca is located more laterally in males (Manuta et al, 2023). Compared to this study, the narrowing of the pelvic cavity is similar to that in cats in male dogs.…”
Section: Discussionsupporting
confidence: 50%
“…Geometric morphometry has proven to be an effective method for sex determination in cats' pelvises (Manuta et al, 2023). Notably, changes were intense in the linea terminalis of the bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometric morphometric analysis of the skull has become increasingly popular in recent years as a method of studying the morphology of various animal species in the field of veterinary anatomy, providing valuable insights into the relationships between different breeds and populations (Gündemir et al., 2023; Hadžiomerović et al., 2023; Manuta et al., 2023; Parés‐Casanova et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, geometric morphometric analysis is a more useful and appropriate method to explain the shape variations [18]. In recent years, various studies using geometric morphometry method in veterinary anatomy have revealed morphometric differences and shape variations among species, breeds and between sexes [16,18,20,26,36].…”
Section: Introductionmentioning
confidence: 99%